Remediation of Arsenic from Water Using ZnCl₂-Activated Sugarcane Bagasse as a Bioadsorbent (Tribhuvan Journal, 2025)
Arsenic contamination in groundwater poses a serious health threat, particularly in developing regions such as the Terai belt of Nepal. This study investigates the efficiency of ZnCl₂-activated sugarcane bagasse (ZnCl₂@SCB) as a low-cost and eco-friendly bioadsorbent for the remediation of As(V) from aqueous solutions. Raw sugarcane bagasse (RSCB) was collected, cleaned, powdered, and chemically activated using ZnCl₂ to enhance its surface porosity. The materials were characterized using FTIR and XRD, confirming the presence of key functional groups and successful incorporation of ZnCl₂ into the biomass structure. Batch adsorption experiments were carried out to evaluate the effects of pH, contact time, and initial arsenic concentration. RSCB exhibited negligible adsorption, whereas ZnCl₂@SCB achieved a maximum removal efficiency of 83.1% at pH 5.0. Equilibrium was reached at 180 minutes, and kinetic modeling revealed that adsorption followed a pseudo-second-order model (R² = 0.999), suggesting chemisorption as the rate-determining mechanism. The Langmuir isotherm provided the best fit (R² = 0.972), with a maximum adsorption capacity (qmax) of 37.03 mg/g. These findings demonstrate that ZnCl₂@SCB is an effective, sustainable, and economically viable bioadsorbent for arsenic remediation in contaminated water systems.